Experimental Investigation on Incorporation of Zinc-Ferrite Nanocoated Baffles for Improving the Performance of Field Power Electrical Transformer Integrated with a Solar Air Heater - Nithiyananthan Kannan; N. Vasantha Gowri; T. Muralikrishna; Avinash Kumar; F. Mary Anjalin; M. Ramesh; B. Muthuraj; Habtewolde Ababu Birhanu (Advances in Materials Science and Engineering)
Solar energy is the most accessible, eco-friendly, and renewable energy source available to meet the world’s expanding energy needs. Solar collectors are commonly utilized to convert solar energy directly into heat for purposes ranging from house heating to timber seasoning and crop drying. The purpose of this research is to design a modified solar air heater (SAH) with a baffle plate and to examine the performance due to the provision of zinc-ferrite nanocoated baffles. The entire system is mounted over a transformer for effective cooling and also produces hot air for industrial requirements. A flat plate collector and a centrifugal blower were used in the experiment. Maximum output air temperatures of 55°C, 62°C, and 72°C were measured for collectors without baffles, baffled collectors, and inverted baffled collectors, respectively. It was also found that the thermal efficiency of flat plate collectors without baffles was 36%, with baffles, it was 44%, and with inverted baffles it was 54%. This study shows that inverted SAH with zinc-ferrite nanocoated baffle plates works better than SAH without baffle plates or with baffle plates in the normal position.